Mechanical behaviors of the brittle rock-like specimens with multi-non-persistent joints under uniaxial compression. (30th September 2019) - Huang, Chenchen; Yang, Wendong; Duan, Kang; Fang, Lindong; Wang, Ling; Bo, Chunjie
Highlights: Mechanical behavior of jointed rock-like specimens is presented. Six failure patterns of specimens are summarized. Orthogonal method analyzing influence degree of geometric parameters of joints. Abstract: The stability of rock engineering applications is significantly influenced by the mechanical behavior of jointed rock masses. However, the deformability, strength and failure characteristics of non-persistent jointed rock specimens have not been examined comprehensively. In this paper, laboratory tests and discrete element method simulations are used to investigate the influence of angle (α), spacing ( S ), joint length ( L ), and rock bridge length ( B ) on uniaxial compressive strength (UCS), Young's modulus and failure processes of brittle rock-like specimens with multi-non-persistent joints. The orthogonal experimental method is used to quantify the influence of four geometric factors on the UCS and Young's modulus through comparing different range values. The results show that the joint inclination angle has the most significant influences on UCS and Young's modulus. The failure patterns can be classified into six categories: (1) stepped path failure caused by wing cracks; (2) stepped path failure caused by wing cracks and shear cracks; (3) vertical failure caused by wing cracks; (4) stepped path failure caused by anti-wing cracks; (5) transfixion failure along the diagonal caused by shear cracks; (6) intact failure. The evolution of micro-cracks divides the numerical stress-strain curve into four stages: stage I, linear elastic stage; stage II, stable development stage of micro-cracks; stage III, increment stage of micro-cracks before peak strength; stage IV, increment stage of micro-cracks after peak strength. Comparison between the experimental and numerical results confirms the capacity of the DEM model to simulate the non-persistent jointed rock specimens. These experimental and numerical results enhance our understanding of the influence of joints on the mechanical behavior of rock masses.